Multibeam bathymetry raw data (Kongsberg EM 712 transit dataset) of RV MARIA S. MERIAN during cruise MSM98 - Miriam Römer; Stefanie Gaide; Anne-Cathrin Wölfl (PANGAEA, 2021)
Multibeam bathymetry raw data was recorded in the North Sea during cruise MSM98 that took place between 2021-01-08 and 2021-01-23. The data was collected using the ship extquotesingles own Kongsberg EM 712. This data is part of the DAM (German Marine Research Alliance) underway research data project.